2021
DOI: 10.3390/microorganisms9081557
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Nutrient Signaling Pathways Conserved in Arbuscular Mycorrhizal Fungi

Abstract: Arbuscular mycorrhizal (AM) fungi form a mutualistic symbiosis with a majority of terrestrial vascular plants. To achieve an efficient nutrient trade with their hosts, AM fungi sense external and internal nutrients, and integrate different hierarchic regulations to optimize nutrient acquisition and homeostasis during mycorrhization. However, the underlying molecular networks in AM fungi orchestrating the nutrient sensing and signaling remain elusive. Based on homology search, we here found that at least 72 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 247 publications
0
16
0
Order By: Relevance
“…The processes of Pi delivery from the arbuscules (or intraradical hyphae) to the periarbuscular space (PAS) (or apoplast) via the specialized transport systems occur in the endomembranes and plasma membranes (PMs) of arbuscules and intraradical hyphae (Ezawa & Saito, 2018; Zhou et al ., 2021). However, the underlying mechanism by which Pi is transported from the fungus to the plant is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes of Pi delivery from the arbuscules (or intraradical hyphae) to the periarbuscular space (PAS) (or apoplast) via the specialized transport systems occur in the endomembranes and plasma membranes (PMs) of arbuscules and intraradical hyphae (Ezawa & Saito, 2018; Zhou et al ., 2021). However, the underlying mechanism by which Pi is transported from the fungus to the plant is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These AM fungal PTs are responsible for absorbing Pi from soil, after which Pi is polymerized into polyphosphate (polyP) through the vacuolar transporter chaperone (VTC) complex in the ERM and transported by the vacuoles (Uetake et al ., 2002; Kikuchi et al ., 2014). Within the IRM, AM fungal exopolyphosphatases Ppx1 and Ppn1 can hydrolyze polyP into inorganic Pi, which is effluxed from the vacuole into the cytoplasm by the unidentified Pi exporter (Aono et al ., 2004; Ohtomo & Saito, 2005; Ezawa & Saito, 2018; Zhou et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Pi transport systems in AMF is very similar to that of Saccharomyces cerevisiae, which is well-known to contain the high-affinity system Pho84p and Pho89p and the low-affinity system Pho87p, Pho90p, and Pho91p (Auesukaree et al, 2003). This suggests that there exists a conserved PHOSPHATE (PHO) signaling pathway between AMF and yeasts (Aono et al, 2004;Olsson et al, 2006;Kikuchi et al, 2014;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…It has been shown that there is a specialized Pi export system in the arbuscules, where free Pi is transported and unloaded into the periarbuscular space (PAS) (Ezawa and Saito, 2018;Zhou et al, 2021;Xie et al, 2022). After the Poly-P hydrolyzation in the IRM and arbuscules, the Pi transporters containing SPX (SYG1/Pho81/XPR1) domains participate in the Pi export process at the symbiotic interface, releasing Pi into the PAS (Ezawa and Saito, 2018;Plassard et al, 2019;Xie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation